2012
DOI: 10.1589/jpts.24.1195
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol on Static Balance in University Students

Abstract: Abstract.[Purpose] The purpose of this study was to compare the participants' balance before and after the alcohol intake.[Subjects] This study conducted experiments by selecting adult subjects between the ages of 19 and 27. Thirty subjects (men=15, woman=15) were arranged into three groups. There were 10 people in each group.[Method] The three groups drank 0.05 mL/kg, 0.4 mL/kg and 0.8 mL/kg of alcohol, respectively. Romberg's test was applied to measure static balance ability. A static balancing ability test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Its diagnostic usefulness for the liver fibrosis of patients with chronic liver disease has been reported by several studies since it was introduced by Sandrin et al 10 ) . Although most studies were conducted using patients with chronic viral hepatitis type C 17 , 18 , 19 , 20 ) , Foucher et al 21 ) included subjects with chronic viral hepatitis, alcoholic hepatitis and steatohepatitis, and reported a significant correlation between liver stiffness and the degree of liver fibrosis diagnosed by biopsy. However, only a few studies have covered the liver biopsies of Asians, whose liver hepatitis has other causes, to investigate the clinical usefulness of liver stiffness measured by FibroScan.…”
Section: Discussionmentioning
confidence: 99%
“…Its diagnostic usefulness for the liver fibrosis of patients with chronic liver disease has been reported by several studies since it was introduced by Sandrin et al 10 ) . Although most studies were conducted using patients with chronic viral hepatitis type C 17 , 18 , 19 , 20 ) , Foucher et al 21 ) included subjects with chronic viral hepatitis, alcoholic hepatitis and steatohepatitis, and reported a significant correlation between liver stiffness and the degree of liver fibrosis diagnosed by biopsy. However, only a few studies have covered the liver biopsies of Asians, whose liver hepatitis has other causes, to investigate the clinical usefulness of liver stiffness measured by FibroScan.…”
Section: Discussionmentioning
confidence: 99%
“…Balance is affected by proprioception, vision, vestibular function, cognitive ability, etc. 1 , 2 ) . Many recent studies have shown that attentional focus of a motor performer may affect balance 3 , 4 , 5 , 6 , 7 , 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the Westerners, Koreans are more likely to get infected by hepatitis, there is a higher repetition rate of liver cirrhosis. 5 , 6 Since the rate of drinking alcoholic beverages is increasing 7 , the occurrence of chronic liver disease is becoming worse. Liver cirrhosis mostly appears when chronic hepatitis due to hepatitis virus is not well treated.…”
Section: Introductionmentioning
confidence: 99%